A Practical E-Test System - Sattar, Zina (International Journal of Emerging Technologies in Learning (iJET), 2019)
this article presents an encryption system which has many characteristics, like anonymity, originality, correctness, confidentiality, durability and confirmation as well as no need to any trusted authority. Besides that the submitted system gives an evidence of the successful submission by using anonymity property. Additional to use the anonymous return channel, also use the timed-based solution. The proposed system has been implemented and its results were measured. The preliminary findings in this paper seem very promising. Also, the results show that the system is applicable and will yield good results if applied to new generations of mobile phones. Furthermore, the results show that the method is more efficient and faster than the system already in place.